Motor learning and control : concepts and applications - Magill, Richard A. (New York : McGraw-Hill, 2011)
Designed for introductory students, this text provides the reader with a solid research base and defines difficult material by identifying concepts and demonstrating applications for each of those concepts.
Includes bibliographical references and indexes.
Keywords: Motor learning -- Textbooks; Motor Activity; Motor Skills